KUALITAS LAPORAN KEUANGAN INSTANSI PEMERINTAH - Deliza Henny I; Sondang Dame Rebecka; Harti Budi Yanti (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2021)
This study aims to determine the effect of human resource competence, the effects of human resources competency, the implementation of the institution accounting system and the internal control system on the quality of financial statements in the Directorate General of Civil Aviation. The number of samples used in this study were 185 respondents with the method of determining the sample is the purposive sampling method. Data collection is carried out by distributing questionnaires to financial officers who are in 173 work units under the Directorate General of Civil Aviation. The results of this study indicate that the effect of human resource competence, the effects of human resources competency, the implementation of the institution accounting system and the internal control system have a positive and significant effect on the quality of financial reports. Tujuan penelitian ini adalah mengungkap peran kompetensi sumber daya manusia, sistem akuntansi instansi dan sistem pengendalian internal terhadap kualitas laporan keuangan Instansi pemerintah. Data penelitian diperoleh dari 185 orang responden yang bertugas pada bagian keuangan. Semua responden berasal dari 173 satuan kerja dibawah Direktorat Jenderal Perhubungan Udara. Hasil penelitian membuktikan secara empiris ketiga variabel tersebut berpengaruh positif terhadap kualitas laporan keuangan instansinya.